Analysis of Almeera Hijab's Marketing Communication Strategy in an Effort to Maintain Consumer Loyalty Amid the Corona Pandemic Outbreak - Khintari, Muhammad Amien; Nur, Dini Hajah; Medi, Ilham; Fauziyah, Azizah; Nurfitriya, Mira (A Social Science and Entrepreneurship Journal, 2021)
The purpose of this study was to determine the loyalty of Almeera Hijab consumers during the Covid-19 pandemic. The research model in this study is to use a qualitative descriptive method, namely the researcher describes and describes the data obtained from the research results then the conclusion is drawn to determine the marketing communication strategy that is in Almeera Hijab. The results of this study are whether or not in the situation of the Covid-19 pandemic, consumer loyalty can still be maintained, even if it does not rule out the possibility of adding new consumers.